Burnout syndrome in non-healthcare workers 2020 - 2024: a scoping review - Soler Saña, Meritxell (2025)
healthcare professionals during the pandemic. Objective: To identify studies that determine the prevalence of burnout syndrome among non-healthcare worker populations between 2020 and 2024. Methods: A scoping review conducted in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. A literature search was carried out in the PubMed and Web of Science databases on 2 January 2025. The Joanna Briggs Institute tool for cohort studies was used to assess methodological quality. Main Results: 12 of the 494 studies retrieved met the inclusion criteria, totalling 12,612 participants from different professions. Asian studies contributed the most of participants, 77.1% (N=9,723). 42% of the studies were conducted in Europe. 50% used the Maslach Burnout Inventory or one of its variants to determine burnout, and 58.3% of the studies correlated burnout with other psychosocial problems and variables. Overall Conclusions: The intervening factors in burnout extend beyond COVID-19, even in groups of non-healthcare workers, suggesting structural and intrinsic organisational causes. Future research should focus on longitudinal studies that identify causal relationships and allow for the design and evaluation of interventions in companies to prevent and avoid psychosocial health problems in workers, involving other groups and regions to obtain a complete global perspective.